A method based on precolumn derivatization and ultra high performance liquid chromatography with high‐resolution mass spectrometry for the simultaneous determination of phthalimide and phthalic acid in tea. Issue 7 (4th March 2019) - Gao, Guanwei; Chen, Hongping; Chai, Yunfeng; Jin, Lili; Liu, Xin; Lu, Chengyin
Abstract: Phthalimide can be formed from either the degradation of folpet and phosmet, or reaction of phthalic anhydride with primary amino groups. Consequently, the sum of phthalimide and folpet, expressed as folpet‐residue definition, is highly prone to false‐positive levels of folpet in tea. An analytical method is thus urgently needed to investigate the residue level and source of phthalimide in tea. In this work, we developed an accurate method of determining phthalimide and phthalic acid (the indicator of phthalic anhydride) by acetonitrile extraction and 3‐bromopropyltrimethylammonium bromide derivatization coupled with ultra high performance liquid chromatography and high‐resolution mass spectrometry. The method was validated, and linearity (correlation coefficients > 0.99) was obtained. Satisfactory recoveries at 10, 20, 50, and 100 μg/kg ranged from 76 to 117%, and the intra‐ and interday accuracies were <23%. The limit of quantification for phthalimide and phthalic acid was 10 μg/kg. The developed method was further successfully used to determine phthalimide and phthalic acid in some tea samples. The positive rate of phthalimide and phthalic acid detected in the tea samples ranged from 30–75 and 50–90%, respectively.